Incidental vocabulary acquisition and gamer perceptions of learning in massive online multiplayer role-playing games - Hussein, Gilan (AUC Knowledge Fountain, 2019)
The present study aims to investigate incidental vocabulary acquisition in massive online multiplayer role-playing games in a non-instructional setting. The purpose of this study is to explore the perceptions of young adult Egyptian online video-gamers of their vocabulary acquisition through game-play. Furthermore, the study aims to discover some of the learning and interaction strategies that these gamers employ in their online discussions and to analyze their potential in promoting vocabulary acquisition. Findings from the analysis of the data gathered from an online questionnaire, semi-structured interviews with some of the participants, and ongoing observations of gamers’ online interactions on game-related discussion forums confirmed the merit of online video-games in encouraging incidental acquisition of vocabulary items in the game. The majority of participants were in consensus regarding their perceptions of their L2 vocabulary acquisition through game involvement. Instances of dual coding, elaborations, error corrections, and questioning provided evidence of some learning strategies and interaction strategies utilized by gamers of online role-playing video-games in learning L2 vocabulary items.